The Resistance of Aedes aegypti to Permethrin 0.25% Insecticide, Malathion 0.8%, and Transfluthrin 25% in the Universitas Islam Bandung Tamansari Campus - Ratna Dewi Indi Astuti; Ismawati Ismawati; Listya Hanum Siswanti (Universitas Islam Bandung, 2019)
Massive and long term insecticide use causes resistance of mosquitos to insecticides. This research has a goal for assessing the resistance of Aedes aegypti to the insecticides of permethrin 0.25%, malathion 0.8%, and transfluthrin 25% in the Universitas Islam Bandung Tamansari campus. The Aedes aegypti resistance in the Universitas Islam Bandung Tamansari campus Bandung city to insecticides measured with the susceptibility test in September 2015. The susceptibility test to the permethrin 0.25% and malathion 0.8% insecticides implemented by using WHO standard instruments and methods. The susceptibility test to transfluthrin 25% implemented by using commercial insecticide according to the usage suggestion. The total mosquitos that died after the exposure of permethrin 0.25%, transfluthrin 25%, and malathion 0.8% for 60 minutes were 20%, 23%, and 80%. The WHO criteria state that mosquitos were still susceptible to insecticides if the death rate is 98–100%, tolerant if the death rate is 80–97%, and mosquitos are resistant if the death rate is less than 80%. In conclusion, the Aedes aegypti mosquitos in the Universitas Islam Bandung Tamansari campus are already resistant to the insecticides permethrin 0.25% and transfluthrin 25% and tolerant to malathion 0.8%. RESISTENSI AEDES AEGYPTI TERHADAP INSEKTISIDA PERMETHRIN 0,25%, MALATHION 0,8%, DAN TRANSFLUTHRIN 25% DI KAMPUS UNIVERSITAS ISLAM BANDUNG TAMANSARIPenggunaan insektisida secara masif dan jangka panjang menimbulkan resistensi nyamuk terhadap insektisida. Penelitian ini bertujuan menilai resistensi resistensi Aedes aegypti terhadap insektisida permethrin 0,25%, malathion 0,8%, dan transfluthrin 25% di kampus Unversitas Islam Bandung Tamansari. Resistensi Aedes aegypti di kampus Unversitas Islam Bandung Tamansari Kota Bandung terhadap insektisida diukur dengan uji kerentanan pada bulan September 2015. Uji kerentanan terhadap insektisida permethrin 0,25% dan malathion 0,8% dilakukan menggunakan alat dan metode uji standar WHO. Uji kerentanan terhadap transfluthrin 25% dilakukan menggunakan insektisida komersial sesuai dengan anjuran penggunaan. Jumlah nyamuk yang mati dalam jangka waktu 60 menit setelah paparan permethrin 0,25%, transfluthrin 25%, dan malathion 0,8% berturut-turut adalah 20%, 23%, dan 80%. Kriteria WHO menyatakan nyamuk dikategorikan masih rentan terhadap insektisida jika tingkat kematiannya 98–100%, toleran jika kematiannya 80–97%, dan resisten apabila jumlah kematian nyamuk kurang dari 80%. Simpulan, nyamuk Aedes aegypti yang terdapat di kampus Universitas Islam Bandung Tamansari telah resisten terhadap insektisida permethrin 0,25% dan transfluthrin 25%, serta toleran terhadap malathion 0,8%.